Urban Heat Island. Assessment techniques, mitigation and applications in a post-socialist city - HERBEL, Ioana (2020)
The expansion without precedent of city boundaries determined the modification of the climatic conditions inside urban areas, with a direct impact on the environment and the population. Urban development implies fundamental changes in the natural setting, generating significant differences between the urban environment and the nearby areas in terms of meteorological parameters, air quality, and energy balance.Over the last decades, cities worldwide have experienced accelerated development, urbanization being one of the most important dimensions of global change. Nowadays 54% of the world population lives in urban areas, being responsible for 76% of the energy consumption and emissions of greenhouse gasses (Grumbler et al. 2012).